Maternal exposure to sulfonamides and adverse pregnancy outcomes: A systematic review and meta-analysis - Li, Peixuan (PLoS One, 2020)
BACKGROUND: Sulfonamides are widely used to treat infectious diseases during pregnancy. However, the safety of maternal exposure to sulfonamides is controversial. This study aims to systematically review the available studies and examine the effect of maternal sulfonamides use on adverse pregnancy outcomes. METHODS: We searched PubMed, Science Direct, Web of Science, ClinicalTrials.gov, CNKI and Wanfang Database (in Chinese). The meta-analysis used random effects model or fixed effects model to obtain the total odds ratio (OR) for each outcome through Stata11.0 software. Study on the relationship between sulfonamide exposure during pregnancy and adverse pregnancy outcomes. The study design covered randomized controlled trials, cohort studies and case-control studies. The study protocol was registered in PROSPERO with protocol number CRD42020178687. RESULTS: A total of 10 studies, and 1096350 participants were included for systematic review. Maternal exposure to sulfonamides was found to be possibly associated with increased risk of congenital malformations (OR = 1.21, 95% CI 1.07–1.37). The use of sulfonamides in the first trimester of pregnancy and during the entire pregnancy might be associated with congenital malformations. CONCLUSIONS: Maternal exposure to sulfonamides may be associated with offspring’ s congenital malformations. Prescription of sulfonamides for pregnant women is suggested to be carefully censored.